SOSIALISASI IMPLEMENTASI PROGRAM PROFIL PELAJAR PANCASILA DI SMP SWASTA SULTAN AGUNG PEMATANGSIANTAR - Sherly Sherly; Herman Herman; Fitria Halim; Edy Dharma; Ridwin Purba; Yanti Kristina Sinaga; Arwin Tannuary (LPPM Universitas Bina Bangsa, 2021)
This community service aims to improve and develop knowledge related to the Pancasila Student Profile program for educators and students. The Pancasila Student Profile Program is one of the Independent Learning programs launched by the Ministry of Education and Culture, which removes the National Examination and is replaced with a Minimum Competency Assessment (AKM) where one component of the AKM is a character survey which is a selected aspect of the six elements of the Pancasila Student Profile, namely faith. Moreover, pious to TYME and have a noble character, global diversity, cooperation, independence, critical and creative reasoning. The objectives of this socialization activity are: 1) Educators and students get to know the Pancasila Student Profile; 2) Educators are willing to implement the Pancasila Student Profile Program through habituation, coaching, and online learning; 3) Educators can implement the Pancasila Student Profile Program through habituation, coaching and online learning; 4) Educators prepare students to face AKM, especially character surveys; and 5) Achieved student Wellbeing